The Bombay interlude: Parsi transnational aspirations in the first Persian sound film. Issue 2 (4th May 2018) - Fish, Laura
ABSTRACT: The focus on cinema in Iran has imbricated the medium within the discourse of Iranian nationalist projects of the twentieth century, expressing the idea of transnationalism as merely the use of non-Iranian locales or actors. This article draws upon the first Persian-language sound film The Lor Girl (1933) to contest the historiography of the film as demonstrative of Iranian nationalism alone. Rather, it argues that the film came out of the Indian Parsi intellectual discourse of the 1920 and 1930s defining Parsi identity in relation to their status in Iran and colonial India and presenting the potential for Parsi transnational colonial desires to gain prestige in Iran. Drawing on textual and discourse analysis of the film and Indian and Iranian reports at the time of its exhibition, this article poses the resilience of the image of Bombay in Parsi cross-border cultural initiatives.